Workplace Mental Health: Application of a Population Health Approach of Proactive Screening to Identify Risk and Engage in Care. Issue 3 (March 2021) - Fragala, Maren S.; Hunter, Jennifer L.; Satish, Anita; Jelovic, Nicole A.; Carr, Susan; Bailey, Allison M.; Stokes, Meghan; Hayward, Joanna I.; Kim, Paul M.; Peters, Matthew E.
Abstract : Objective: To evaluate a proactive, voluntary screening program designed to identify employees with emerging mental health risk and engage them in care. Methods: Risk was proactively identified through online screening of 344 participants. At-risk participants were offered a mental health care concierge to provide support, develop a care plan, and connect to care. Results: Risk for common mental health conditions was identified in 244 (71%) participants, of whom 66 (27%) connected with a care concierge. Compared with participants who did not connect to a care concierge, those who did were more likely to report a financial crisis (68.2% vs 50.8%) and less likely to report verbal abuse (9.1% vs 19.6%) and difficulty meeting daily needs (12.1% vs 25.1%). Conclusion: Implementation of this screening program identified employees at risk for mental health conditions and facilitated connection to care.